The broken table. The Detroit newspaper strike and the state of American labor - Rhomberg, Chris (New York, 2012)
" When the Detroit newspaper strike was settled in December 2000, it marked the end of five years of bitter and violent dispute. No fewer than six local unions, representing 2,500 employees, struck against the Detroit News, the Detroit Free Press, and their corporate owners, charging unfair labor practices. The newspapers hired permanent replacement workers and paid millions of dollars for private security and police enforcement; the unions and their supporters took their struggle to the streets by organizing a widespread circulation and advertising boycott, conducting civil disobedience, and publishing a weekly strike newspaper. In the end, unions were forced to settle contracts on management's terms, and fired strikers received no amnesty."